A randomized, double-blind, placebo controlled trial to evaluate the efficacy and safety of probiotic preparation in children with acute Diarrhea - Sankar S, Siva; Kumar R, Arun; S, Kavitha; S, Vijayarangan; R, Ezhil Arasan (Edelweiss Applied Science and Technology, 2025)
To investigate the efficacy of probiotic preparation in the management of acute diarrhea in children, 100 children (aged 3 months to 5 years) were randomized into 2 groups – probiotic and control group. The probiotic group received Bacillus Clausii - 2 billion, Streptococcus Thermophilus St-21 – 100 million, Bacillus coagulans - 50 million, and Bacillus mesentericus TO-A - 1 million twice a day for 7 days. The control group received a placebo twice a day for 7 days. Both groups received ORS and Zinc. The mean duration of diarrhea was shorter in the probiotic group (2.90 ± 0.86 days) compared to the control group (4.0 ± 1.16 days), p<0.001. Patients in the probiotic group exhibited rapid improvement in terms of a decrease in the frequency of episodes of diarrhea within 48-72 hours. Most patients in the probiotic group recovered from diarrhea on the 2nd and 3rd day, compared to the 4th and 5th day in the control group. The probiotic preparation was found to be effective in the management of acute diarrhea in children and was well tolerated without any adverse effects. Thus, probiotics should be considered an integral part of the management of diarrhea.